Performance Analysis of Photovoltaic Passive Heat Storage System with Microencapsulated Paraffin Wax for Thermoelectric Generation - Nazer, Mohamed; Rostam, Muhammad Fadzrul Hafidz; Eh Noum, Se Yong; Hajibeigy, Mohammad Taghi; Shameli, Kamyar; Ali Tahaei (Journal of Research in Nanoscience and Nanotechnology, 2021)
The depletion of non-renewable energy sources and negative effects towards the environment push research towards the widespread adoption of renewable energy sources such as solar energy. The main drawback of solar panels is that temperatures above 27°C will result in an efficiency drop of 0.1-0.5%/°C. In previous studies, usage of photovoltaic thermal (PVT) systems was mainly for the purpose of heating water, warming buildings, and drying crops. This research will focus on the usage of a standalone PVT and thermoelectric generator (TEG) system whereby it uses heat extracted from the PVT system for thermoelectric generation. A passive standalone PVT-TEG system design with microencapsulated paraffin wax as a phase change material (PCM) as a heat storage medium was created. The heat stored in the PCM is used as a heat source for thermoelectric generation. To extract the heat from the PV panel, an aluminum heatsink underneath the PV panel is used as a heat absorber to passively extract heat without external power sources. This setup reduces the surface temperature by 22.7°C. Transient thermal analysis and thermoelectric simulation of the system was conducted through Computational Fluid Dynamics (CFD) using ANSYS 2019 software. The error recorded between the experimental and simulation results was 4.2%. This proposed system panel successfully increased the electrical efficiency of the PV panel by approximately 12.8%, where the overall electrical power produced shows a significant increase from 7.7W to 17.7W.